ANALISIS STABILITAS NILAI TUKAR MATA UANG ASEAN-10 TERHADAP DOLAR AS DAN DINAR EMAS - Basyariah, Nuhbatul; Khairunnisa, Hafsah (EQUILIBRIUM, 2016)
This study aimed to determine the stability of ASEAN-10 currency exchange rate on US Dollar and Gold Dinar. It used quantitative descriptive method with variation coefficient. The results indicated that the ASEAN-10 currency is not stable toward US Dollar and Gold Dinar. It is caused by the ASEAN-10 currencies which rely on US Dollar exchange rate that tends to fluctuate. When the variation coefficient is smaller, the currencies will be more stable. Based on the variation coefficient calculation, ASEAN-10 currency which has smallest to largest variation coefficient are Riel Cambodian, New Kip Laos, Baht Thai, Peso Philippine, ringgit Malay, rupiah Indonesia, Dollar Singapore, Dollars Brunei, Kyat Myanmar, and Dong Vietnam. Then, the stability on gold dinar, Rupiah Indonesia tends to be weak. The comparison of US Dollar and Gold Dinar stability is not significant where US dollar is more stable than the Gold Dinar.